Can Immune Thrombocytopenia Be Cured with Medical Therapy? - Cuker, Adam; Prak, Eline T. Luning; Cines, Douglas B. (Seminars in Thrombosis and Hemostasis, 2015)
Primary immune thrombocytopenia (ITP) in adults often assumes a chronic course that requires persistent monitoring and treatment. Medical therapy has traditionally been viewed as a means of temporarily raising the platelet count with little or no potential to induce long-term platelet responses off treatment. However, several recent studies have tested the hypothesis that intensive medical therapy administered early in the disease course may ameliorate or even cure ITP. In this review, we propose a biological rationale for medical intervention that simultaneously targets the innate and adaptive immune responses administered early in the course of disease. We also critically examine data on long-term outcomes after single-agent and multi-agent medical therapy. Intensive regimens that target inflammation and adaptive immunity (e.g., combination high-dose dexamethasone and rituximab) appear to improve response rates at 6 to 12 months compared with standard first-line therapy (e.g., prednisone, high-dose dexamethasone alone) in newly diagnosed patients. Controlled trials with extended follow-up are needed to determine whether these intensive regimens induce more cures compared with standard treatment or merely delay relapse at the expense of potentially greater toxicity.
Keywords: immune thrombocytopenia; treatment; cure; remission